Extreme spawning-site fidelity in Atlantic cod - Skjaeraasen, J E; Meager, J J; Karlsen, Ø; Hutchings, J A; Ferno, A (ICES Journal of Marine Science, 2011)
Based on a 3-year mark-recapture study, evidence is provided of spawning-site fidelity in Atlantic cod (Gadus morhua) at a scale (<1 km) smaller than documented previously. Coastal regions where barriers to dispersal exist may allow for local population dynamics and adaptation to develop in broadcast-spawning marine fish at extremely fine spatial scales.